Somatic Genetic Mosaicism in the Apolipoprotein E-null Mouse Aorta - Valencia-Morales, María del Pilar; Sanchez-Flores, Alejandro; Colín-Castelán, Dannia; Alvarado-Caudillo, Yolanda; Fragoso-Bargas, Nicolás; López-González, Gladys; Peña-López, Tania; Ramírez-Nava, Magda; de la Rocha, Carmen; Rodríguez-Ríos, Dalia; Lund, Gertrud; Zaina, Silvio (Thrombosis and Haemostasis, 2021)
In addition to genetic and epigenetic inheritance, somatic variation may contribute to cardiovascular disease (CVD) risk. CVD-associated somatic mutations have been reported in human clonal hematopoiesis, but evidence in the atheroma is lacking. To probe for somatic variation in atherosclerosis, we sought single-nucleotide private variants (PVs) in whole-exome sequencing (WES) data of aorta, liver, and skeletal muscle of two C57BL/6J coisogenic male ApoE null/wild-type (WT) sibling pairs, and RNA-seq data of one of the two pairs. Relative to the C57BL/6 reference genome, we identified 9 and 11 ApoE null aorta- and liver-specific PVs that were shared by all WES and RNA-seq datasets. Corresponding PVs in WT sibling aorta and liver were 1 and 0, respectively, and not overlapping with ApoE null PVs. Pyrosequencing analysis of 4 representative PVs in 17 ApoE null aortas and livers confirmed tissue-specific shifts toward the alternative allele, in addition to significant deviations from mendelian allele ratios. Notably, all aorta and liver PVs were present in the dbSNP database and were predominantly transition mutations within atherosclerosis-related genes. The majority of PVs were in discrete clusters approximately 3 Mb and 65 to 73 Mb away from hypermutable immunoglobin loci in chromosome 6. These features were largely shared with previously reported CVD-associated somatic mutations in human clonal hematopoiesis. The observation that SNPs exhibit tissue-specific somatic DNA mosaicism in ApoE null mice is potentially relevant for genetic association study design. The proximity of PVs to hypermutable loci suggests testable mechanistic hypotheses.
Keywords: ApoE null mouse; atherosclerosis; aorta; somatic genetic mosaicism